Development of an Online Nomogram for Predicting Postoperative Hypoalbuminemia in Older Adults Following Femoral Neck Fractures - Gong H; Miao H; Hong W; Yu W; Sun Y (Clinical Interventions in Aging)
Han Gong,1,* Haixiang Miao,1,* Weishi Hong,1 Wenlong Yu,2 Yu Sun1 1Department of Orthopedics, Northern Jiangsu People’s Hospital Affiliated to Yangzhou University, Yangzhou, Jiangsu, People’s Republic of China; 2Department of Orthopedics, Dalian Medical University, Dalian, Liaoning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Sun, Email docsunyu@126.comObjective: Postoperative hypoalbuminemia after total hip arthroplasty (THA) in older adults with femoral neck fractures can increase the risk of postoperative infection and lengthen hospital stays. The purpose of this study was to construct an online nomogram that can be used for the clinical preoperative assessment of older adults to reduce the incidence of postoperative complications.Methods: This study included older adults who underwent THA for femoral neck fracture at Northern Jiangsu People’s Hospital between December 2018 and April 2022. Univariate and multivariate logistic regression analyses were performed for the training cohort to identify independent risk factors. The area under the ROC curve (AUC), calibration curve, and decision curve analysis (DCA) of the training group (n=306) and the validation group (n=131) were plotted to assess the model performance.Results: Multivariate logistic regression analysis revealed 5 independent risk factors, including Age, body mass index (BMI), surgery time, preoperative blood calcium level, and preoperative erythrocyte sedimentation rate (ESR). We constructed a nomogram, and the area under the curve (AUC) of the nomogram was 0.763 (95% CI 0.705– 0.820) for the training group and 0.750 (95% CI 0.665– 0.835) for the validation group. The calibration curve showed good consistency between the predicted and actual probabilities. Decision curve analysis (DCA) showed that using the nomogram had a high net benefit.Conclusion: Old age, lower BMI, longer surgery time, preoperative blood calcium level and preoperative ESR are independent risk factors for postoperative hypoalbuminemia after THA in older adults with femoral neck fractures. The online nomogram had high predictive values for to predict clinical postoperative hypoalbuminemia older adults with femoral neck fracture.Keywords: total hip arthroplasty, hypoalbuminemia, dynamic nomogram, older adults, femoral neck fractures